Genetic and Neuroimaging Features of Personality Disorders: State of the Art - Ma, Guorong; Fan, Hongying; Shen, Chanchan; Wang, Wei (Neuroscience bulletin, 2016)
Personality disorders often act as a common denominator for many psychiatric problems, and studies on personality disorders contribute to the etiopathology, diagnosis, and treatment of many mental disorders. In recent years, increasing evidence from various studies has shown distinctive features of personality disorders, and that from genetic and neuroimaging studies has been especially valuable. Genetic studies primarily target the genes encoding neurotransmitters and enzymes in the serotoninergic and dopaminergic systems, and neuroimaging studies mainly focus on the frontal and temporal lobes as well as the limbic-paralimbic system in patients with personality disorders. Although some studies have suffered due to unclear diagnoses of personality disorders and some have included few patients for a given personality disorder, great opportunities remain for investigators to launch new ideas and technologies in the field.